Research on STEM Education: A Bibliometric Review of Literature Over the Past 20 Years - Tiurma Juniar P. Nababan (Journal of Technology-Assisted Learning, 2025)
In recent years, Science, Technology, Engineering, and Mathematics (STEM) education has emerged as a major focus in countries worldwide. This study employs bibliometric analysis to assess the scientific output on STEM education indexed in the Scopus database between 2004 and 2024. Bibliometric software was used to visualize the data. This software provides a range of analytical functions, enabling the examination of various bibliometric indicators, such as publication counts, citation frequencies, authorship networks, and keyword co-occurrence networks. A total of 3,769 publications were retrieved for analysis. The findings highlight a significant surge in scientific output over the past four years, accounting for 71% of the total publications. International Journal of STEM Education emerging as the leading journal. The USA leads with 4,086 publications, followed by China and Turkey with 671 and 327, respectively. The most productive authors are affiliated with the top 10 universities and research institutions. Three keywords that frequently appear are technology, student, and education. The research spans both foundational and interdisciplinary topics, addressing STEM education across various levels, including primary and secondary schools, undergraduate studies, and computational education. The findings from such analysis can also inform the development of educational and research policies, supporting strategic decisions in advancing STEM education and research initiatives.